Ski is involved in transcriptional regulation by the repressor and full-length forms of Gli3 - Dai, Ping (Cold Spring Harbor Laboratory Press, 2002)
Transcription factor Glioblastoma-3 (Gli3) is cleaved in the anterior region of the limb bud to generate its repressor form. In contrast, Sonic hedgehog (Shh) signaling from the posterior zone of polarizing activity blocks Gli3 processing and then induces the expression of Gli3 target genes, including Gli1. Here we report that the Ski corepressor binds to Gli3 and recruits the histone deacetylase complex. The Gli3-mediated repression was impaired by anti-Ski antibody and in Ski-deficient fibroblasts, and Shh-induced Gli1 gene transcription mediated by full-length Gli3 was inhibited by Ski. Furthermore, a Ski mutation enhanced the digit abnormalities caused by the Gli3 gene mutation. Thus, Ski plays an important role in pattern formation.